P835 Smoking cessation in IBD: What are the predictive factors?. (16th January 2018) - Martinho-Grueber, M; Biedermann, L; Schöpfer, A; Vavricka, S; Clair Willi, C; Fournier, N; Allez, M; Macpherson, A J; Juillerat, P
Abstract: Background: Smoking cessation should be also recommended by all physicians in inflammatory bowel disease (IBD) as its worsens the course of disease in Crohn's patients (CD), but is not a good option for ulcerative colitis (UC) patients, however rather protective, because of its extraintestinal deleterious effects. In our previous cross-sectional study, former smokers were older males with a higher body mass index (BMI) and CD patients with isolated ileal disease and UC patients with a less extensive disease were more likely to succeed in smoking cessation. We currently aimed to evaluate prospectively these findings. Methods: Adult IBD patients were prospectively included in the Swiss IBD cohort from November 2006 to November 2015. They were asked about their smoking status at enrolment and during the follow-up (total of 2361 patients). We identified active smokers with a change of smoking status during follow-up suggesting a successful cessation of tobacco consumption and matched them to a group of patients continuing to smoke. Results: 2367 IBD patients (1368 CD, 999 UC) were included in the analysis. We identified 125 CD and 40 UC active smokers who ceased tobacco consumption during the follow-up. The most predictive factor for smoking cessation in CD patients was the involvement in a relationship (OR 1.9, p < 0.01), whereas it had no impact in UC patients. Gender, duration of illness, BMI, disease activity or location, stenosing or perforating complications and having surgeries were not predictive factors for cessation of tobacco. Conclusions: Being in a relationship is a favourable factor for smoking cessation in CD patients. This result raised awareness on the importance of the role of the partner and possibly social network of our patients in the process. This should change our practice towards promoting the implication of the partner in this important decision